The Parish Edition effects of the church publication on church leaders and parishioners - Concepcion, Lailani Mananay 1980-
This is a descriptive study on the effects of Church publications on the members of the parish community. Using media effects theories and the uses of gratifications approach, it aimed to know how the publications affect both the church leaders and the parishioners. Survey, content analysis, and key informant interviews were employed to gather the essential data for the study. The sample was taken from the five parishes on the Diocese of Malolos that have regular publications. Ten Church leaders were interviewed while 80 parishioners were randomly selected for the survey. The three most recent issues of the Church publications were included for the content analysis. The Church publications have two main roles in the parish, information and evangelization. Thus, the things printed in the publication also report the different events and other concerns of the local community. The parishioners generally like the content and presentation of the Church publications, and they even want more pages, more copies, and frequent issues, although they would like to seek improvements on the printing particularly of the pictures and illustrations. In addition, they want literary section and column for the youth and kids to be included un the publications. It was found out that the parishioners read the publications to know what is happening in the parish and to know more about the faith. The readers have high level of exposure to and strong degree of involvement with the Church publications. They miss it when it does not come and even ask or borrow copy from others. They like practically everything that is written in the publication most especially the one authored by the priest. Although there were no established effects of the Church publication to the parishioners, it was observed that more exposed and involved readers tend to be members of an organization, more frequent mass goers, more familiar with the church leaders, and, more aware and supportive if Church projects. To the Church leaders, these publications serve as compensation for the voluntary work that they do by acknowledging their accomplishments. This inspires them to improve their work and helps them to respond to what the parishioners need.